Psychosocial Suicide Prevention Interventions in the Elderly: A Mini-Review of the Literature - Zeppegno, Patrizia; Gattoni, Eleonora; Mastrangelo, Martina; Gramaglia, Carla; Sarchiapone, Marco (Frontiers in Psychology, 2019)
In Europe the elderly population is projected to increase from 18.5% (93.9 million) in 2014 to 28.7% (149.1 million) by 2080. In the USA it is estimated that by the year 2030 more than 20% of the population will be aged 65 years or over. This specific population is at high risk of unrecognised or untreated psychiatric illnesses and suicide. It is well known that completed suicide rate increases with age in both men and women. Although elderly people attempt suicide less often than other age groups, they show a higher completion rate. Generally the methods chosen by elderly are more lethal, the intent is more serious, they are more determined and they show fewer warning sign than the younger population. A recent systematic review and meta-analysis of psychosocial intervention following self-harm in adults found that cognitive behavioural therapy was the most effective in these patients. Unfortunately there have been few reported trials of other potentially effective interventions. Because the scientific literature on psychosocial suicide prevention interventions in the elderly is still scant we decided to conduct a mini-review in order to take stock of the situation. Studies were identified through electronic searches of the Cochrane library, MEDLINE, Scopus and Web of Science databases. PRISMA guidelines were followed and only 7 articles met the inclusion criteria. No firm conclusions can be drawn about this topic because there is still little data and studies used inconsistent outcome measures and designs. Nonetheless, the existing data suggests that psychosocial interventions are promising.